Differentiating between serial, hybrid and parallel dimensional metrology - Wenig, Elisa; Grömme, Ulrich; Hausotte, Tino (Sensoren und Messsysteme, 2022)
This article deals with the definition of the terms “serial metrology” and “parallel metrology” and the necessity to revise the existing definition to lay the basis of a clear and comprehensible classification of the metrology of multidimensional position or coordinate measuring systems (CMSs). The need for the revision is exemplarily shown with the classification of different CMSs according to the existing definition and the discussion of the results of it. Subsequently the revised definition for the given terms is proposed and the definition of the term “hybrid metrology” is added. Finally the re-classification of the chosen CMSs according to the revised definition is shown.<br
Keywords: parallel; serial; metology; parallel metrology; serial metrology; micrometrology; nanometrology; Parallelmetrologie; Seriellmetrologie; Mirkomesstechnik; Nanomesstechnik